TAMAÑO DE SEMILLA Y SU RELACIÓN CON LA CALIDAD FÍSICA Y FISIOLOGICA EN VARIEDADES COMERCIALES DE TRIGO (Journal on studies and research of academic knowledge, 2017)
The research was carried out with the objective of determining the effect of seed size and its relationship with physical and physiological quality on wheat varieties. The experiment also aims to determine the effect of seed size on weight of one thousand seeds, to evaluate the effect of seed size on the percentage of germination in field, plant height, ear size, weight of fifty ears, grain weights per spike, among others. The research was carried out at the farm located in San Juan del Paraná State of Itapúa. The experimental design used in the field was completely randomized blocks with four replicates with factorial arrangement. The varieties used were 4, they were: Itapúa 65, Itapúa 75, Itapúa 80 and CD-1252. With the studied it is possible to verify that the varieties of big size T1, have a higher percentage of germination and emergence, as well as plant height at 90 days after sowing, by weight of 1,000 seeds there are no differences between size T1 and T2, as well as the size of spike after 90 days is better in size T1, as well the spike size after 90 days is better in size T1. The varieties of size T2, present germination speed because the water absorption is faster. Taking account the dry soil or water deficiency that could be noticed throughout the cycle, from planting on June 13 to the harvest on October 14, 2016.
Keywords: seed sizes; germination; seed weight planting